2023
DOI: 10.3389/fmed.2023.1195026
|View full text |Cite
|
Sign up to set email alerts
|

A human pilot study on positive electrostatic charge effects in solid tumors of the late-stage metastatic patients

Ashkan Zandi,
Fatemeh Shojaeian,
Fereshteh Abbasvandi
et al.

Abstract: BackgroundCorrelative interactions between electrical charges and cancer cells involve important unknown factors in cancer diagnosis and treatment. We previously reported the intrinsic suppressive effects of pure positive electrostatic charges (PEC) on the proliferation and metabolism of invasive cancer cells without any effect on normal cells in cell lines and animal models. The proposed mechanism was the suppression of pro-caspases 3 and 9 with an increase in Bax/Bcl2 ratio in exposed malignant cells and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…We observed that 4T1 TNBC cells undergo apoptosis when treated with iEFs in vitro . This finding is notable, especially in the context of bioelectricity, as other methods of applying electrical current or fields, such as tumor treating fields 47 (TTFs) and positive electrostatic charge therapy 48,49 (PECT), have also reported selective apoptosis of cancer cells. In addition, a recent study showed that TTFs enhance anti-tumor immune activation in a murine glioblastoma (GBM) model 50 .…”
Section: Discussionmentioning
confidence: 95%
“…We observed that 4T1 TNBC cells undergo apoptosis when treated with iEFs in vitro . This finding is notable, especially in the context of bioelectricity, as other methods of applying electrical current or fields, such as tumor treating fields 47 (TTFs) and positive electrostatic charge therapy 48,49 (PECT), have also reported selective apoptosis of cancer cells. In addition, a recent study showed that TTFs enhance anti-tumor immune activation in a murine glioblastoma (GBM) model 50 .…”
Section: Discussionmentioning
confidence: 95%